2008
DOI: 10.1080/07357900701638418
|View full text |Cite
|
Sign up to set email alerts
|

The Growth-Inhibitory Effects of Dexamethasone on Renal Cell CarcinomaIn VivoandIn Vitro

Abstract: DEX treatment is a candidate for advanced RCC therapy by inhibiting the activation of NF-kappa B and its downstream products such as IL-6, IL-8 and VEGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…This observation is in agreement with our findings. In addition, molecular studies using reverse transcriptase PCR showed that GR mRNA is expressed in several RCC cell lines [27,28]. Our study is the first to provide immunohistochemical and molecular evidence of strong GR expression in most CRCCs.…”
Section: Discussionmentioning
confidence: 65%
“…This observation is in agreement with our findings. In addition, molecular studies using reverse transcriptase PCR showed that GR mRNA is expressed in several RCC cell lines [27,28]. Our study is the first to provide immunohistochemical and molecular evidence of strong GR expression in most CRCCs.…”
Section: Discussionmentioning
confidence: 65%
“…Intracellular IL-6, as well as those in the conditioned medium, was downregulated in all cell lines following treatment. Concentrations of IL-8 in the conditioned medium were remarkably decreased in NC65 cells, while VEGF secretion was lowered by 30-65% in all RCC lines, with the inhibition of the nuclear translocation of NF-κB (65). After therapy with dexamethasone, cases of complete regression (CR) occurred, and the cases included patients with metastases located in the brain and lungs.…”
Section: Glucocorticoid Receptors (Gr)mentioning
confidence: 99%
“…As TRAILs induce apoptosis only in tumor cells, they may be a promising cancer treatment, and medications such as RU486 may be a novel strategy for the recovery of TRAIL sensitivity in cancer cells otherwise resistant to TRAIL (62). In a study conducted by Arai et al (65), the inhibitory effects of dexamethasone (DEX) on the growth of RCC in vivo and in vitro were examined and suppression of NF-κB activation was measured. DEX binds more powerfully to the glucocorticoid receptor than cortisol.…”
Section: Glucocorticoid Receptors (Gr)mentioning
confidence: 99%
“…In addition, molecular studies utilizing reverse transcriptase polymerase chain reaction (RT-PCR) revealed that most commonly used RCC cell lines express high levels of GR. In a study by Arai et al, two RCC cell lines OUR-10 and NC65 expressed high levels of GR, whereas Caki-1 cell exhibited low levels of GR expression by Western blot (Arai et al 2008). Iwai et al demonstrated GR mRNA expression in the A498, RCC270, Caki1, and ACHN renal carcinoma cells.…”
Section: Expression Of Gr In Kidney Tumorsmentioning
confidence: 99%
“…Signaling through GRs in renal cancer cells involves suppression of other transcription factors, including nuclear factor kB, AP-1, CREB, CCAAT enhancer binding protein (C/EBP), signal transduction activator of transcription (STAT), p53, Smad, etc (De Bosscher et al 2003). Treatment of RCC cell lines with glucocorticoids (dexamethasone) inhibits the activation of nuclear factor kB and its downstream products including IL-2, IL-6, IL-8, and vascular endothelial growth factor which have been demonstrated to promote growth of RCC cell lines (Arai et al 2008;Iwai et al 2004;Miki et al 1989;Takenawa et al 1995). Glucocorticoids have long been used as anti-inflammatory drugs, and have been beneficial in the treatment of hematopoietic neoplasms (multiple myeloma) and solid malignancies such as hormone-refractory prostate cancer (Greenstein et al 2002;Storlie et al 1995).…”
Section: Expression Of Gr In Kidney Tumorsmentioning
confidence: 99%